Lithium chloride inhibits infectious bronchitis virus-induced apoptosis and inflammation. (January 2022) - Liu, Xingyun; Chang, Xinyu; Wu, Qin; Xu, Jun; Chen, Lu; Shen, Ruiting; Hou, Xiaolin
Abstract: Avian infectious bronchitis (IB) was caused by infectious bronchitis virus (IBV), a coronavirus, which leads to enormous economic losses in the poultry industry. Studies have shown that lithium chloride (LiCl) is a good virus inhibitor. Through cell culture, virus infection, and RT-qPCR, we found that LiCl could down-regulate the apoptosis-related genes Caspase-3 and Bax, up-regulate Bcl-2, and down-regulate the inflammatory-related genes (NF-κB, NLRP3, TNF-α, and IL-1β) via inhibiting virus replication. Finally, clinical trials showed that LiCl could inhibit IBV-induced apoptosis and inflammatory in chicken embryos as well as reduce the mortality and deformity rate of chicken embryos. The results showed that LiCl has antiviral activity against IBV and clinical effects. Further studies are required to explore the exact action mechanism of LiCl on IBV-induced apoptosis and inflammation. Highlights: LiCl inhibits IBV-induced apoptosis and inflammation in vitro. LiCl inhibits IBV-induced apoptosis and inflammation in chicken embryos. Effect of LiCl on IBV replication in vitro and in chicken embryos.